Computational Neuropsychiatry – Schizophrenia as a Cognitive Brain Network Disorder - Dauvermann, Maria R.; Whalley, Heather C.; Schmidt, André; Lee, Graham L.; Romaniuk, Liana; Roberts, Neil; Johnstone, Eve C.; Lawrie, Stephen M.; Moorhead, Thomas W. (Frontiers in Psychiatry, 2014)
Computational modelling of functional brain networks has advanced the understanding of higher cognitive function. It is hypothesised that functional networks mediating higher cognitive processes are disrupted in people with schizophrenia. In this article, we review studies that applied measures of functional and effective connectivity to fMRI data during cognitive tasks, in particular working memory fMRI studies. We provide a conceptual summary of the main findings in fMRI data and their relationship with neurotransmitter systems, which are known to be altered in individuals with schizophrenia. We consider possible developments in computational neuropsychiatry, which are likely to further our understanding of how functional networks are altered in schizophrenia.